PENDAMPINGAN PEMULIHAN KONDISI PETERNAKAN AYAM RAS PETELUR PASCA GEMPA DI KABUPATEN LOMBOK UTARA - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Erwan Erwan; Ketut Gede Wiryawan (Jurnal Gema Ngabdi, 2019)
An earthquake that occurred from the end of July to the end of August 2018 in the province of NTB has detroyed not only residential buildings, offices, schools, religious buildings, but also livestock houses, especially the houses and cages. Almost all districts in the NTB province was affected by the earthquake and the worst affected districts were North Lombok and East Lombok. The Norty Lombok Regency is currently experiencing total paralysis both in the fields of education, government and economics and tourism. One business that requires rapid handling in the field of animal husbandry is for egg production. There are 26 poultry farmers who are members of the "Telur Jaya" breeders group supplying eggs for the community and visitors in North Lombok district. Because of the earthquake, this group was unable to produce eggs to meet the needs of the people of in North Lombok district due to destroyed housing conditions, many chickens died, and chickens which were survive received improper management and attention. The initial step taken was to recover laying hens housing and managemnt. Cage capacity for 26 breeders ranges from 250 to 2200 birds were repaired using cage materials that can still be used and new materials to replace damaged materials. Mentoring activities continue to be carried out so that poultry farmers can run their businesses so they can supply egg needs in North Lombok Regency.